AI-powered chatbot integrated with WhatsApp for automatic invoice generation in a service company - Alvarado Huaman, Brayan Junior Jhonatan; Saenz Cabanillas, Anibal German; Sierra-Liñan, Fernando (LACCEI, 2025)
Manual invoice processing in small service companies often leads to delays, human errors, and inefficient administrative workflows. This study presents the design and implementation of an intelligent chatbot integrated with WhatsApp, which aims to automate the generation of electronic invoices through voice commands. The system combines AI-based natural language processing, low-code automation (n8n), and official validation services, such as the SUNAT API, to extract, validate, and structure billing data. Real-world testing at Servicios Generales Alvarado Hns demonstrated a significant reduction in processing time (from 9 to 10 minutes to less than 2 minutes per invoice) and the elimination of billing errors. User satisfaction reached an average score of 4.65, validating the system's usability and effectiveness. The results confirm that AI-based mobile solutions can improve administrative efficiency in micro and small businesses, especially in mobile operating environments.